2019
DOI: 10.3354/dao03421
|View full text |Cite
|
Sign up to set email alerts
|

Pathological findings and survey for pathogens associated with reproductive failure in perinatal Steller sea lions Eumetopias jubatus

Abstract: Steller sea lions (SSLs) Eumetopias jubatus experienced a population decline in the 1960s, leading to the listing of the western stock as endangered and the eastern stock as threatened under the US Endangered Species Act. A decrease of births in the western stock beginning in the late 1960s indicates that reproductive failure may have contributed to the decline. We evaluated the role pathogens play in spontaneous abortions, premature births and neonatal deaths in SSLs. Archived tissues from carcasses (n = 19) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
(81 reference statements)
1
5
0
Order By: Relevance
“…A previous study on Steller sea lions in Alaska found Chlamydia spp. (Esquible et al 2019). Further evidence that justified the present research is the findings of Chlamydia psittaci in water birds from New Zealand and water birds kept in a wildlife rescue center from the west of France, in the North Atlantic (Aaziz et al 2015, Soon et al 2021.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…A previous study on Steller sea lions in Alaska found Chlamydia spp. (Esquible et al 2019). Further evidence that justified the present research is the findings of Chlamydia psittaci in water birds from New Zealand and water birds kept in a wildlife rescue center from the west of France, in the North Atlantic (Aaziz et al 2015, Soon et al 2021.…”
supporting
confidence: 59%
“…In Alaska, Brucella spp. was detected in Steller sea lions (Eumetopias jubatus) (Esquible et al 2019). However, other countries, such as New Zealand, have failed to identify whether brucellosis affects sea lions (Roe et al 2010).…”
mentioning
confidence: 99%
“…However, B. pinnipedialis infection in cetaceans has rarely been associated with pathology [ 22 , 23 ]. Furthermore, Brucella ST 27 has been identified in a single Steller sea lion ( Eumetopias jubatus ) in Alaska’s waters [ 24 ], highlighting the need for continued monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…PDV is closely related to CDV, and primarily infects animals in the family Phocidae. PDV infection has also been reported in other pinnipeds, such as the walrus ( Odobenus rosmarus ), sea lion ( Eumetopias jubatus ), and New Zealand fur seal ( Arctocephalus forsteri ) 62–64 . It has also been reported that PDV infects animals in the family mustelidae (sea otters and minks) 65,66 .…”
Section: Epidemiology Of Current Morbillivirus Speciesmentioning
confidence: 92%
“…PDV infection has also been reported in other pinnipeds, such as the walrus (Odobenus rosmarus), sea lion (Eumetopias jubatus), and New Zealand fur seal (Arctocephalus forsteri). [62][63][64] It has also been reported that PDV infects animals in the family mustelidae (sea otters and minks). 65,66 In the North Atlantic to Arctic region, there have been large PDV outbreaks in the past, and it is speculated that the virus circulates in the region.…”
Section: Phocine Morbillivirusmentioning
confidence: 99%